Analysis Of Induction Motor With Broken Bars And Constant Speed Using Circuit-field Coupled Method - Halem, N.; Zouzou, S. E.; Srairi, K. (University of Eloued جامعة الوادي, 2011)
The paper presents the use of the two-dimensional finite element method for modeling the three-phase squirrel-cage induction motor by using circuit coupled method. In order to analyze the machine performances, the voltage source is considered. The Ansys magnetic analysis software is used for calculating the magnetic field of an induction motor having a cage fault. The experimental results prove that the proposed approach constitutes a useful tool for the study and diagnostics of induction motors.
Articale in Journal of fundamental and Applied Sciences Vol. 03 N. 01
Keywords: Induction motor, finite element, broken rotor bars, time stepping finite element (TSFE), spectra.